2019
DOI: 10.1113/jp277775
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia impairs uterine artery function in pregnant mice

Abstract: Key pointsr Obstructive sleep apnoea (OSA) is a chronic condition characterized by intermittent hypoxia that induces oxidative stress and inflammation leading to cardiovascular disease.r Women can develop OSA during late pregnancy, which is associated with adverse maternal and fetal outcomes. However, the effects of OSA throughout pregnancy on fetoplacental outcomes are unknown.r Using a mouse model of intermittent hypoxia, we evaluated main uterine artery function, spiral artery remodelling, circulating angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…The present study was carried out in a sheep model rather than the most commonly used rodent models that have previously explored the effects of maternal OSA on the fetus and offspring (3,13,35,36,38). A minor, but certainly not negligible, advantage of the ovine model is that the size of both mother and fetus (usually single gestation) are very close to those in humans, thereby facilitating local measurements and tissue biopsy at different fetal organs and, most importantly, allowing for implantation of telemetric sensors to monitor physiological signals in the developing fetus subjected to maternal OSA from mid to late gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was carried out in a sheep model rather than the most commonly used rodent models that have previously explored the effects of maternal OSA on the fetus and offspring (3,13,35,36,38). A minor, but certainly not negligible, advantage of the ovine model is that the size of both mother and fetus (usually single gestation) are very close to those in humans, thereby facilitating local measurements and tissue biopsy at different fetal organs and, most importantly, allowing for implantation of telemetric sensors to monitor physiological signals in the developing fetus subjected to maternal OSA from mid to late gestation.…”
Section: Discussionmentioning
confidence: 99%
“…25,28,33,39,61), OSA poses a specific challenge during pregnancy. Indeed, both clinical and animal studies have shown that OSA imposes significant risk accrual for the emergence of diabetes and preeclampsia in pregnant women, and increased risk for metabolic syndrome is apparent in offspring both short term and long term and is even transmitted across generations (3,13,35,36,38,52,69).…”
Section: Introductionmentioning
confidence: 99%
“…There is increased recognition that OSA, characterized by intermittent hypoxia (IH), is deemed as a risk factor for the development of many cardiovascular diseases such as hypertension [ 4 ], myocardial ischemia [ 6 ], heart failure [ 7 ], atherosclerosis [ 17 ], and coronary artery disease [ 18 ]. The IH leads to a number of potential adverse consequences, including activation of inflammation [ 19 ], insulin resistance [ 20 ], oxidative stress [ 21 ], sympathetic activation [ 22 ], and endothelial dysfunction [ 23 ]. Thus, it contributes to OSA-associated cardiovascular pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was carried out in a sheep model rather than the most commonly used rodent models which have previously explored the effects of maternal OSA on the fetus and offspring (3,13,35,37,40). A minor, but certainly not negligible advantage of the ovine model is that the size of both mother and fetus (usually single-gestation) are very close to those in humans, thereby facilitating local measurements and tissue biopsy at different fetal organs and most importantly, allowing for implantation of telemetric sensors to monitor physiological signals in the developing fetus subjected to maternal OSA from mid to late gestation.…”
Section: Discussionmentioning
confidence: 99%
“…increase in morbidity and mortality by cardiocirculatory, metabolic, neurocognitive and malignant diseases (25,28,33,38,61), OSA poses a specific challenge during pregnancy. Indeed, both clinical and animal studies have shown that OSA imposes significant risk accrual for the emergence diabetes and pre-eclampsia in pregnant women, while increased risk for metabolic syndrome is apparent in offspring both shortterm and long-term, and even transmitted across generations (3,13,35,37,40,52,69).…”
Section: Introductionmentioning
confidence: 99%